2016
DOI: 10.1002/aenm.201600923
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Charge Collection Limitation at Solid/Liquid Interface by a Controllable Crystal Deficient Overlayer

Abstract: Bulk and surface charge recombination of photoelectrode are two key processes that significantly hinder solar‐to‐fuel conversion of photoelectrochemical cell (PEC). In this study, the function of a “crystal‐deficient” overlayer is unveiled, which outperforms a traditionally used amorphous or crystalline overlayer in PEC water splitting by exhibiting a high conductivity and large electron diffusion length to enable unlimited electron collection. The optimized ≈2.5 nm thickness of the “crystal‐deficient” shell r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 49 publications
(55 reference statements)
0
62
0
1
Order By: Relevance
“…The IPCE of H–TiO 2 for T wire = 1700 °C shows the best redshift of band edge (bandgap narrowing) and the best improvement of visible photoactivity. Recently, two effective and practical hydrogenation approaches using either lithium reduction or Pd‐catalyzed instant hydrogenation could achieve the maximum 2 mA cm −2 photocurrent density at 1.23 V versus RHE. In comparison to the photocurrent density of these superior hydrogenation methods, our approach achieved 2.5 mA cm −2 photocurrent density, 25% enhancement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The IPCE of H–TiO 2 for T wire = 1700 °C shows the best redshift of band edge (bandgap narrowing) and the best improvement of visible photoactivity. Recently, two effective and practical hydrogenation approaches using either lithium reduction or Pd‐catalyzed instant hydrogenation could achieve the maximum 2 mA cm −2 photocurrent density at 1.23 V versus RHE. In comparison to the photocurrent density of these superior hydrogenation methods, our approach achieved 2.5 mA cm −2 photocurrent density, 25% enhancement.…”
Section: Resultsmentioning
confidence: 99%
“…The Al‐reduced amorphous shell is proved to be responsible for the improved visible‐light absorption. Zhang et al revealed that the disordered shell trapped photogenerated holes and promoted the charge separation . Therefore, developing novel approaches to modify black TiO 2 with the disordered shell is critical to achieve enhanced PEC activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of the TiO 2 -MoS 2 heterojunction and the Ti 3+ species narrowed the band gap of TiO 2 , leading to the excellent activity in photocatalytic degradation of methyl orange and water splitting for H 2 evolution under visible-light irradiation [85]. The H 2 production rates were 0, 0.13, 0.32, and 0.56 mmol·h [86,87]. Typically, 14 mg of metallic Li foils were dissolved in 20 mL of ethanediamine under dry conditions; then, 200 mg of TiO 2 nanocrystals (Degussa P25) was immersed into the ethanediamine solution for 6 h with continuous stirring; 1 M HCl was used to consume the excess Li or electrons when the reaction was complete; finally, the product was rinsed with deionized water several times and dried in vacuum oven at room temperature [86].…”
Section: Magnesium Reductionmentioning
confidence: 87%
“…Furthermore, Zhang et al found that the "crystal-deficient" layers on the surface of the rutile TiO 2 nanowires increased the conductivity by 50 times, which increased the electron diffusion length to~20 μm and overcame the charge collection limitation at the solid/liquid interface for efficient conversion of solar energy to chemical energy [87]. These studies highlight the importance of controlling the surface localization of defects and the solid/liquid interface towards enhanced photoactivity over TiO 2 photocatalysts [86][87][88]. 9 International Journal of Photoenergy [30].…”
Section: Magnesium Reductionmentioning
confidence: 99%